ANALISIS SISTEM INFORMASI GEOGRAFIS PARIWISATA DI KABUPATEN SEMARANG - Wahyudi, Irawan Parulian; Papilaya, Frederik Samuel (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2024)
As time goes by, technology is also developing, especially in the field of Geographic Information Systems (GIS). Geographic Information Systems (GIS) have become an important tool in analyzing, managing, and designing. In various fields and sectors. Semarang Regency is a region located in the province of Central Java which has many very diverse tourist destinations. Tourist destinations in Semarang Regency are relatively low in visitors compared to other regions. Therefore, the aim of this research is to design an application that functions to introduce tourist destinations in Semarang Regency to the wider community by adopting Geographic Information System (GIS) technology. This application makes it easier for visitors to find out tourist locations, see locations virtually using images, see place ratings based on public assessments, looking at the costs required to access tourist areas, etc. This design method uses qualitative methods and system design using UML (Unified Modeling Language)